A Systematic Review of Enterprise Architecture Adoption Models - Ahmad, Nor Azizah; Drus, Sulfeeza Mohd.; Abu Bakar, Nur Azaliah; Othman, Mohd Muneer (International Journal of Engineering and Technology, 2018)
This article provides a systematic review of the Enterprise Architecture (EA) adoption model. Firstly, an analysis of the literature discussing the current EA adoption models was undertaken. The EA adoption models were reviewed to identify which adoption phase can be connected.Â  This paper also discusses the limitations of the models. Based on the inclusion and exclusion criteria defined in the review process, 13 articles were reviewed.Â  There are 13 different EA adoption models across the number of adoption phases which were selected from 13 articles. A total of 11 adoption models were designed for the post-adoption phase and applicable for the EA implementation phase and two (2) adoption models were formulated for adoption phase. This SLR reflected that there was relatively little research conducted in the adoption phase. Previous scholars had adopted one or a combination of different underpinning theories in their studies to identify the existing approach and perspective formulating EA adoption model. The finding also revealed the limitation of previous studies such as generalizability and fragmented perspective. Therefore, this review will provide further investigation into the potential development of EA adoption model at an early stage that could provide wide-ranging and rational views of business, information, and technology for the organisation.